Interaction of Lamb Waves with Domain Walls in an Iron Borate Plate - E.A. Zhukov; M.E. Adamova; A.V. Kaminsky; A.P. Kuz’menko; V.I. Zhukova (Журнал нано- та електронної фізики)
This work presents the calculation results of the Lamb wave spectra in a plate of iron borate. Experimental data on how flexural vibrations in a borate plate influence its domain structure are provided.